Šalčius and his textbook of arithmetics - Ažubalis, Algirdas (Lietuvos matematikos rinkinys, 2010)
Matas Šalčius (1890–1940) was a teacher, journalist, public man and traveler. In addition to his other important works, he compiled a textbook of arithmetic in Lithuanian for adults while residing in USA during the World War One.
Keywords: teacher; journalist; public man; traveler; textbook of arithmetic; USA; adults